Agricultural Productivity, Regional Inequality and Development Strategies in Latin America and Sub-Saharan Africa - Thurlow, James; Morley, Sam; Nin-Pratt, Alejandro; Dorosh, Paul (2010)
James Thurlow, Sam Morley, Alejandro Nin-Pratt and Paul Dorosh International Food Policy Research Institute